trigonometric problem

Asked by  | 30th Aug, 2008, 05:37: PM

Expert Answer:

we can write x = x+y-y

so sin(x) = sin( (x+y) - y )

sinx = k sin(x+2y)   => sin( (x+y) - y ) = k sin( (x+y) + y )

sin(x+y) cosy - cos (x+y) siny = k ( sin(x+y) cosy + cos (x+y) siny )

divide the whole equation by cosy cos(x+y)

tan(x+y) - tany = k ( tany + tan(x+y) )

(1-k) tan(x+y) = (1+k) tany

tan(x+y) = (1+k) / (1-k)   tany

Answered by  | 12th Sep, 2008, 09:41: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.